Combined thermal and mechanical finite element modeling of roller-compacted concrete dam - Abdulrazeg, Aeid A. (2012)
Roller compacted concrete (RCC) dams are vulnerable to cracking as a result of high tensile stresses due to thermal loads, material properties and mechanical loads. Making reliable prediction of stress fields, and thereby cracking risk, thermal and mechanical properties such as creep form an important part of the material modeling. Recently, many models have been proposed to study the significance of thermal loads and creep on RCC dam. Most of the earlier researchers considered creep very approximately or neglected it altogether. However, due to the significant influence of creep on the stress values, especially in early age concrete, a more accurate creep model is essential. Furthermore, most of the previous researchers who investigated dam concrete mainly focused on the uniaxial compressive and tensile strength, so their studies did not consider safety of the dam concrete under multi-axial stress states. In this investigation, a system of crack prediction of RCC dam during construction and operation phase has been developed. It takes into account more relevant features of the behavior of concrete such as ageing, temperature effect, creep and adiabatic temperature. Appropriate boundary conditions in the dam body is used for the water interaction at the upstream face of the dam, taking into account the variation of temperature of the reservoir water with depth. The primary objectives of the present work are:  To formulate a new viscoelastic model, which includes the ageing and temperature effect on properties of concrete.  To propose a mathematical crack model for RCC materials, which includes the effect of aging and temporal domain on its formation to reliably establish a precise safety evaluation of the RCC dam behavior.  To develop a system of crack prediction of RCC dam. Hence a viscoelastic model, which involves ageing effects and thermal dependent properties, is adopted for the concrete. The maturity concept (degree of hydration) was introduced to describe the development of material properties such as elastic modulus and tensile strength. The influence of different isothermal temperatures on creep is taken into account by the maturity concept and a transient thermal creep term is introduced. In order to assess the occurrence of crack either at short or long term in RCC dams, a mathematical crack model for RCC materials which consider most of the crucial factors such as aging and temperature effect, variation of mechanical properties and current stress state on its formation to establish more reliable safety evaluation of the RCC dam behavior is proposed. In context of the finite element method, all the above proposed mathematical model were formulated. The existing finite element programs have been extensively modified to include the above issues (viscoelastic model, aging and temperature effect and mathematical crack model). The validation of the developed finite element programs has been done at two stages, firstly based on experimental evidences and secondly based on analytical evidences. Regarding the experimental evidences, the developed programs were verified against the monitoring temperatures measured by insulating thermocouples in two full real scale tests of RCC dams. The predicted results obtained from the finite element programs were found to be in good agreement with the measured ones. The modified finite element programs were used to solve some numerical examples reported in literature and the predicted results were found to be consistent with the reported ones. The developed system has been applied to assess the temperature distribution and stress fields of the 65 m height Zirdan RCC dam under hot- dry climate action during the construction and operation phases. In this investigation, alternative studies considering different construction schedules were performed to evaluate their effect on the safety assessment of the dam. The results have shown that, an alternative placing schedule with the stoppage and avoidance of summer work improved the level of safety in the dam. Furthermore, the developed system has been applied for the determination of the thermal and structural response and evaluates the level of safety of an unsymmetrical double curvature arch concrete dam during the construction stage. The result has shown that, high tensile stresses have been observed at the dam bottom and the abutment boundaries in the upstream side section due to the restriction from the abutment and foundation rock.